ANALISIS FENOMENA UNDERPRICING IPO DENGAN BOARD SIZE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang Melakukan IPO di Bursa Efek Indonesia Tahun 2020 – 2024) - Khoirun Nisa’; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze and obtain empirical evidence on the effect of financial leverage, the use of IPO proceeds for investment, underwriter reputation, profitability, and firm size on the level of underpricing with board size as a moderating variable. The study focuses on companies that conducted an IPO on the Indonesia Stock Exchange (IDX) during the period 2020 and 2024. This study employs secondary data obtained from IPO prospectuses listed on the Indonesia Stock Exchange. The total population consist of 288 companies that conducted an IPO during the 2020–2024 period. Sample selection was carried out using a purposive sampling method based on criteria established by the researcher, resulting in a final sample of 268 companies that experienced underpricing during their IPO. The analytical method employed in this study is Moderated Regression Analysis (MRA). The results of this study indicate that financial leverage, the use of IPO proceeds for investment, profitability, and firm size has a positive effect on underpricing, whereas underwriter reputation does not have a significant effect on underpricing. Furthermore, board size is proven moderate the relationship between financial leverage and underpricing. However, board size fails to moderate the relationships that the use of IPO proceeds for investment, profitability, and firm size with the level of underpricing.